Recurrent Plasmacytomas after Allografting in a Patient with Multiple Myeloma - Allen N. Stawis; Diane Maennle; Moreno Festuccia; Zia Uddin; Benedetto Bruno (Case Reports in Medicine)
Extramedullary recurrence in multiple myeloma patients has been reported after both autologous and allogeneic hematopoietic cell transplantation and, more recently, after treatment with so-called new drugs with potent antimyeloma activity. Only a very few sizable reports focused on its clinical presentation and its incidence, which may be highly underestimated, and most observations are based on single patients reported from several institutions. Given the unusual sites of recurrence, diagnosis may be rather difficult and delayed treatment may play a relevant role in prognosis. Here we report a case of a myeloma patient, initially treated with an allograft, who enjoyed an eleven-year disease-free remission with very good quality of life. She eventually relapsed first with an extramedullary plasmacytoma in the breast and, two years later, with a right atrial cardiac mass.